The activity of being : an essay on Aristotle's ontology - Kosman, Louis Aryeh (Harvard University Press, 2013)
Understanding "what something is" has long occupied philosophers, and no Western thinker has had more influence on the nature of being than Aristotle. Focusing on a reinterpretation of the concept of energeia as "activity," Aryeh Kosman reexamines Aristotle's ontology and some of our most basic assumptions about the great philosopher's thought.